An Analysis of Difficulties in Using Quantifier Faced by the Eight Grade Students at SMP Angkasa Lanud Padang in The Academic Year 2022/2023 - Rita Nurmansyah; Jufrizal Jufrizal (Journal of English Language Teaching, 2023)
This research is aimed to find out the eighth-grade students’ difficulties in using quantifiers and  to find out the factors that cause the students’ difficulties. This research used a mixed-method research design. The instruments of this research are multiple-choice test and  interview. In this research there were 25 students at the eight one class students and also the English teacher of SMP Angkasa Lanud Padang as the  sample. The techniques of collecting the data were test with 40 questions and interview with 6 questions. The findings of the research show that all students are categorized as failing. There are three difficulties faced by the students; difficulty remembering and using the quantifier appropriately, difficulty in understanding the countable and uncountable noun word, difficulty remembering the vocabularies. There are some factors that cause the students’ difficulties in using quantifiers were classified into two categories. First, the cause of students’ difficulties related to the learning process, are two factors; the teacher explained the material too quickly and sometimes the teacher's method of teaching was boring. Second, the factors that cause students’ difficulties related to students, there are three factors; lack of vocabularies, lack of motivation, carelessness. This research is expected useful for the English language teaching and learning process at SMP Angkasa Lanud Padang.